Modelling forest systems (CABI, 2003)
This book, containing 34 papers presented at a workshop held in Portugal in June 2002, reviews current thinking on various models and presents applications in several contexts in relation to forest ecosystems. Topics covered include: forest reality and modelling strategies; mathematical approaches and reasoning; estimation processes and models; validation and decision making under uncertainty; and model archives and metadata. This book will be of significant interest to those in areas of forestry, applied ecology, and statistics and economics.